2014
DOI: 10.1016/j.epsl.2014.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing modern stalagmite growth from cave monitoring, local meteorology, and experimental measurements of dripwater films

Abstract: . (2014) 'Reconstructing modern stalagmite growth from cave monitoring, local meteorology, and experimental measurements of dripwater lms.', Earth and planetary science letters., 392 . pp. 239-249. Further information on publisher's website:http://dx.doi.org/10.1016/j.epsl.2014.02.036Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Earth and Planetary Science Letters. Changes resulting from the publishing process, such as peer review, editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Moreover, the application of multiple proxies contained within speleothems can be used to narrow the range of possible palaeoclimatic and palaeoenvironmental interpretations. The site-specific nature of many reconstructions is reliant on site monitoring, hydrologic modelling, and karst theory (Baker et al, 2014;Fischer and Treble, 2008).…”
Section: Speleothemsmentioning
confidence: 99%
“…Moreover, the application of multiple proxies contained within speleothems can be used to narrow the range of possible palaeoclimatic and palaeoenvironmental interpretations. The site-specific nature of many reconstructions is reliant on site monitoring, hydrologic modelling, and karst theory (Baker et al, 2014;Fischer and Treble, 2008).…”
Section: Speleothemsmentioning
confidence: 99%
“…Estimation of cave ventilation is possible directly via anemometers, indirectly via measurement of levels of radon gas ( 222 Rn) (Kowalczk and Froelich, 2010;Hakl et al, 1997;Faimon et al, 2006;Oh and Kim, 2011) and other tracer gases (De Freitas et al, 1982), or by studies of air density contrasts and thermal patterns within the cave (Faimon et al, 2012;Smithson, 1991;SanchezCanete et al, 2013). The importance of understanding specific cave ventilation mechanisms has been well highlighted in recent studies (Kowalczk and Froelich, 2010;Cowan et al, 2013;Mattey et al, 2010;Baker et al, 2014), as the distinct nature of ventilation in individual caves can negate general assumptions regarding the seasonality of carbonate precipitation. For example, Mattey et al (2010) identified unusual seasonal ventilation regimes in New St. Michaels Cave, Gibraltar, where the summer season was typified by low cave-air pCO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 concentration of cave atmosphere is directly linked to the growth rate of stalagmites (Dreybrodt, 2012;Baker et al, 2014). Growth rate variations can bias the speleothem climate record and lead to changes in the incorporation of trace elements into the crystal lattice (Fairchild et al, 2006;Gabitov & Watson, 2006).…”
Section: Diurnal Variations In Temperature Andmentioning
confidence: 99%
“…Growth rate variations can bias the speleothem climate record and lead to changes in the incorporation of trace elements into the crystal lattice (Fairchild et al, 2006;Gabitov & Watson, 2006). Increased cave ventilation leads to lower pCO 2 values in the cave atmosphere and accordingly lower calcium equilibrium concentration which increases carbonate precipitation rates (Baker et al, 2014). Even though it rains more in the summer, speleothems in CL are expected to grow faster during the low pCO 2 winter season, all other things being equal.…”
Section: Diurnal Variations In Temperature Andmentioning
confidence: 99%
See 1 more Smart Citation